Semiconductor quantum dots - Bányai, L. (World Scientific, 1993)
The book develops the theoretical background material for the analysis of carrier quantum-confinement effects, it introduces different confinement regimes for absolute or center-of-mass motion quantization of the electron-hole-pairs, and it gives an overview of the best approximation schemes for each regime. A detailed discussion of the carrier states in quantum dots is presented, including variational calculations, a configuration interaction approach, and quantum Monte Carlo techniques. Surface polarization instabilities are analyzed which lead to the self-trapping of carriers near the surface of the dots and the influence of spin-orbit coupling on the quantum-confined carrier states is discussed. The linear and nonlinear optical properties of small and large quantum dots are analyzed in detail, including transient optical nonlinearities (photon echo) and two-photon transitions. The influence of the quantum-dot size distribution in many realistic samples is outlined, including the analysis of quantum dot growth laws and universal size distributions.